Bisnis UMKM di Era Digital: Pentingnya Literasi Keuangan - Pranogyo, Antaiwan Bowo; Tarsono, Ono; Elliyana, Ela; Hendro, Junaidi; Sumampouw, Ruland Willy Jack; Ikhsan, Muhammad; Elvira, Elvira (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2024)
The development of digital technology is changing the business paradigm of MSMEs. Digital financial literacy is key to optimizing the potential of technology, managing finances effectively, and protecting oneself from the risks of online transactions. In fierce competition, digital financial literacy supports increased customer trust and builds loyalty through a safe and efficient transaction experience. On this basis, counseling is needed for MSME players as a contribution to community service, especially in overcoming the low level of digital financial literacy among MSME players. To overcome this problem, online soft skills training on entrepreneurship development with a focus on digital financial literacy was conducted. This program improves the digital financial literacy of MSME players, optimizes financial management, improves operational efficiency, and builds business sustainability in the digital era.